Antipyretic activity of the new 2-(((3-mercapto-5-methyl-4н-1,2,4-triazol-4-yl)imino)methyl)-5-r-benzoates - Kravchenko, Tatyana; Panasenko, Оleksandr; Knysh, Yevgen (ScienceRise: Pharmaceutical Science, 2018)
Temperature rise is an important defensive mechanism of the body that activates immune system and increases phagocytosis, suppressing viral and microbial growth. Antipyretic activity, which involves the increase of thermolysis through angiectasis of skin vessels and heightened sweat production, is largely connected with a relaxing effect on the diencephalon’s thermoregulation centers’ irritation that may be altered due to disease. Body temperature higher than 39°C poses a threat to human health, including people of any age, from kids to adults of all ages. Despite analgesics’ high effectiveness, their use is not entirely safe. The use of aspirin impairs blood coagulation and increases the risk of inflammatory processes in gastroenteric tract and causes angiasthenia. The search and study of the new highly effective antipyretic medicines is greatly relevant nowadays. The aim of this work is to conduct a pharmacological screening over the new antipyretic drugs, specifically the derivatives of 2-(((3-mercapto-5-methyl-4Н-1,2,4-triazol-4-yl)imino)methyl)-5-R-benzoate that were obtained for the first time. Materials and methods. The objects of the research were the new 2-(((3-mercapto-5-methyl-4Н-1,2,4-triazol-4-yl)imino)methyl)-5-R-benzoate derivatives. The experimental fever was caused in white nonlinear rats by administrating 2,4-dinitrophenol (2,4-DNP), a dividing agent in oxidative phosphorylation, at the dose of 20 mg/kg. Acetylsalicylic acid was administrated to the reference group of animals at the dose of 100 mg/kg. The substances of research were administrated in 30 minutes (Т0,5) after rats received 2,4-DNP, body temperatures were recorded during 1 hour (Т1). The initial rectal temperature (Т0) was recorded prior the abdominal injection of 2,4-DNP. Acetylsalicylic acid was used as a reference substance at the dose of 100 mg/kg. Results and discussion. The results of the experiment established that in 30 minutes after the abdominal injection of 2,4-DNP, body temperature in the population of rats (n=133) was in range from 37.36 °C to 38.37 °C on average (ΔТ=0.88°C). As for the reference substance acetylsalicylic acid, it caused a 3 % decrease of body temperature in rats with a modeled pathology (ΔТ=-1.2 °С, р≤0.05) with relation to the reference group. The results demonstrated that antipyretic activity of some of the substances was better than that of the reference substance. Hence, substances IV, V, and VIII decreased body temperature in rats by more than 0.39 %. Among the studied entities, substances IV and V are the most promising; they decreased body temperature in rats by 4.66-4.95 %, or by 1.19-2.10°C, with relation to the reference group. Conclusions New 2-(((3-mercapto-5-methyl-4Н-1,2,4-triazol-4-yl)imino)methyl)-5-R-benzoate derivatives were obtained. Ammonium 2-(((3-mercapto-5-methyl-4Н-1,2,4-triazol-4-yl)imino)methyl)-5-R-benzoate is the most active substance. Introduction of inorganic cations leads to the loss of activity. Introduction of piperedinium leads to a slight increase of activity, but still it is weaker than that of the reference substance